Trophic dynamics of three sympatric anuran species in a soybean agroecosystem from Santa Fe Province, Argentina - Peltzer, Paola (2010)
The conversion of forests to agroecosystems presents a challenge for biodiversity conservation. In this study, the feeding habits of three species of anurans (Rhinella fernandezae, Odontophrynus americanus and Physalaemus albonotatus) were comparedRhinella fernandezae, Odontophrynus americanus and Physalaemus albonotatus) were compared between a soybean field and a native forest in Santa Fe Province, Argentina. Our dietary assessment is based on 124 individuals (47 R. fernandezae, 45 O. americanus and 32 P. albonotatus). Lepidopteran larvae were the predominant item in anuranR. fernandezae, 45 O. americanus and 32 P. albonotatus). Lepidopteran larvae were the predominant item in anuran diets from the soybean field, whereas collembola, isopods and snails prevailed in the diets from forests. Generally, the three anuran species shifted their diets as prey differs in the two environments, but R. fernandezae and P. albonotatus maintainedR. fernandezae and P. albonotatus maintained a preference for a few prey types. Mean niche overlap in the soybean field was smaller than expected by chance, suggesting that the three anuran species are competing for limited resources. Trophic studies on other native anurans in agroecosystems should be a priority in conservation efforts due to their potential use as natural control agents, as well as for assessing the consequences of the broad conversion of natural forest to agricultural use in our region and throughout the world.